2023
DOI: 10.1021/acs.jpclett.3c00105
|View full text |Cite
|
Sign up to set email alerts
|

Cubic or Not Cubic? Combined Experimental and Computational Investigation of the Short-Range Order of Tin Halide Perovskites

Abstract: Tin-based metal halide perovskites with a composition of ASnX3 (where A= MA or FA and X = I or Br) have been investigated by means of X-ray total scattering techniques coupled to pair distribution function (PDF) analysis. These studies revealed that that none of the four perovskites has a cubic symmetry at the local scale and that a degree of increasing distortion is always present, in particular when the cation size is increased, i.e., from MA to FA, and the hardness of the anion is increased, i.e., from Br– … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…On the contrary, the near-edge portion of the spectrum is much less affected by static and dynamic disorder, and its sensitivity to symmetry and overall geometry (whether or not multiple scattering contributions play a role, as seen in this case) provide an idea complement to diffraction analysis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the near-edge portion of the spectrum is much less affected by static and dynamic disorder, and its sensitivity to symmetry and overall geometry (whether or not multiple scattering contributions play a role, as seen in this case) provide an idea complement to diffraction analysis …”
Section: Resultsmentioning
confidence: 99%
“…32−34 On the contrary, the near-edge portion of the spectrum is much less affected by static and dynamic disorder, and its sensitivity to symmetry and overall geometry (whether or not multiple scattering contributions play a role, as seen in this case) provide an idea complement to diffraction analysis. 35 The understanding of structure−property relations is of pivotal importance for the future development of halide perovskites for solar cells with improved power conversion efficiency, one of the many fields of prospected application.…”
Section: Isotropic Expansionmentioning
confidence: 99%
“…A significant challenge hindering the practical use and advancement of metal halide perovskites pertains to the harmful nature of their primary component, lead (Pb). 1–3 The adverse impacts of lead on the environment and human well-being have raised substantial concerns, underscored by prevailing regulations in various countries that restrict the use of heavy metals. 4 Consequently, there exists a continually increasing fascination with innovative lead-free halide perovskite configurations, encompassing both bulk films and nanocrystals (NCs).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have highlighted the crucial role played by the dynamic local structure and octahedral tilting in halide perovskites . For example, some investigations have revealed that ignoring the local structure can lead to inaccurate interpretation of various experimental techniques, including X-ray absorption near edge structure spectroscopy, high-energy resolution inelastic X-ray scattering, and pair distribution function analysis. Moreover, electronic structure calculations performed for simulation cells corresponding to the average perovskite structure have been shown to result in poor estimates of band gaps, emphasizing that it is critical to account for transient local distortions. These findings underscore the importance of understanding the dynamic nature of halide perovskites and its implications for a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%